Softpower or Hardpower?Some Issues on India’s and China’s Antarctic Programs - Witker, Ivan (2014)
This paper states that even though the Antarctic Treaty is a remarkable instrument for peaceful collaboration and scientific research, it is, basically, a by-product of the Cold War that reaffirms a particular status quo. This paper explores whether the ATS will meet the needs of an emerging world order. Particularly, the paper evaluates the ATS in the face of new global challenges, both internal and external to the Antarctic Treaty System (ATS) itself, as well as power shifting processes on a world scale, climate change and the changing interests of new states. China is a key component in understanding this issue because its Antarctic engagement is entering a new phase one that challenges current multilateral provisions. China’s Antarctic program will be analyzed within the framework of International Relations approaches and theories.